BIM-to-IGA: A fully automatic design-through-analysis workflow for segmented tunnel linings. (October 2020) - Ninić, Jelena; Bui, Hoang Giang; Meschke, Günther
Highlights: A fully parametric design model for segmented tunnel linings. An IGA framework for accurate and computationally efficient design assessment. A fully automated design-through-analysis workflow for tunnel linings. We show that the IGA computational approach outperforms FE analysis for the same problem. A kilometre-long tunnel section can be designed and assessed within 20 min. Abstract: Both planning and design phase of large infrastructural project require analysis, modelling, visualization, and numerical analysis. To perform these tasks, different tools such as Building Information Modelling (BIM) and numerical analysis software are commonly employed. However, in current tunnel engineering practice, there are no systematic solutions for the exchange between design and analysis models, and these tasks usually involve manual and error-prone model generation, setup and update. In this paper, focussing on tunnelling engineering, we demonstrate a systematic and versatile approach to efficiently generate a tunnel design and analyse the lining in different practical scenarios. To this end, a BIM-based approach is developed, which connects a user-friendly industry-standard BIM software with effective simulation tools for high-performance computing. A fully automatized design-through-analysis workflow solution for segmented tunnel lining is developed based on a fully parametric design model and an isogeometric analysis software, connected through an interface implemented with a Revit plugin. The IGA-Revit interface implements a reconstruction algorithm based on sweeping teachnique to construct trivariate NURBS lining segment geometry, which avoids the burden to deal with trimmed geometries.